The Anthology in Digital Culture Forms and Affordances - Taurino, Giulia (Amsterdam University Press, 2023)
As a cultural form, media practice and organizational model, the anthology has represented an important editorial framework in the development, preservation and retrieval of narratives, from paper-based media to machine-generated content, all throughout a series of discontinued analog and digital technologies. Over time, anthologies became part of the "metaphors we live by" (Lakoff and Johnson 2008), figurative lenses through which we read, navigate, interpret stories and organize human thoughts for better understanding. By providing an overview on the role of the anthology on streaming platform environments, this book examines how traditional editorial practices of anthologization intersect with data-driven content classification and sorting in the context of both pre- and post-digital culture. The author ultimately proposes to insert "anthology" in a vocabulary of digital culture that accounts for new curatorial and algorithmic processes of content filtering, in the attempt to expand the critical "keywords" (Williams 1983; Striphas 2015; Thylstrup et al. 2021) for the study of culture, society, data.